ANALISIS SEKTOR EKONOMI UNGGULAN KABUPATEN JOMBANG TAHUN 2011-2015 - Mohamad Basori; Wahyu hidayat; Sudarti Sudarti (Jurnal Ilmu Ekonomi JIE, 2017)
Economic growth and the ongoing process in the main condition for the survival or regional economic development. To carry out the construction focused to the development of the sectors which provide a large effect on the others sectors or the overall economy. The research to know about the leading sector in Jombang Regency. As material consideration in economic development. The research using the cross section data Gross Regional Domestic Product on the basis of constant prices the province East Java and Jombang Regency 2011-2015. The research used analytical location quotient, shift share and index of specialization. Based on the result of the location quotient is there are 9 economic sectors are considered be leading sector is mining and extracting sector, industry processing sector, electricity and gas sector, water procurement, trash processed, and recycling, transportation and warehousing sector, financial services and insurance sector, company sector, construction sector, healthy services sector. The result of the Shift Share analysis indicates the specialization sector is electricity and gas sector, construction sector, procurement accommodation, information and communication sector, real estate sector, and the others services sector.Keyword: Leading Sector Economy, Analysis Location Quotient, Shift Share Analysis, Index of Specialization